Exposure risk assessment of the municipal waste collection activities during COVID-19 pandemic - Loganathan Salvaraji; Mohammad Saffree Jeffree; Richard Avoi; Azam Atil; Hazalina Mohd AKhir; Shamsul Bahari Shamsudin; Khamisah Awang Lukman (SAGE Publishing, 2020)
An increasing amount of waste concurrently further extends the risk of exposure to hazardous material among waste collectors. In light of the COVID-19 crisis, municipal waste collectors are one of the most at-risk groups of SARS-Cov-2 exposure. Risk assessment included hazard identification, evaluation of existing control level at the workplace, estimation of likelihood and severity of hazard, risk determination, and control measure recommendations. Five waste collection activities were identified and reviewed. High-risk exposure includes collection of garbage, mechanical manipulation of compactor lorries and unloading of garbage at the disposal site. There is poor practice of personal hygiene and unestablished continuous monitoring of personal protective equipment supplies. The preventive measures in the waste collection industry are influenced by several factors. Until the preventive measures are adopted into practice and adapted according to each company's requirements, biological agents continue to be risk factor to the health workers.